Transcranial Direct Current Stimulation of the Temporoparietal Junction and Inferior Frontal Cortex Improves Imitation-Inhibition and Perspective-Taking with no Effect on the Autism-Spectrum Quotient Score - Nobusako, Satoshi; Nishi, Yuki; Nishi, Yuki; Shuto, Takashi; Asano, Daiki; Osumi, Michihiro; Morioka, Shu (Frontiers in Behavioral Neuroscience, 2017)
Lesions to brain regions such as the temporoparietal junction (TPJ) and inferior frontal cortex (IFC) are thought to cause autism-spectrum disorder (ASD). Previous studies indicated that transcranial direct current stimulation (tDCS) of the right TPJ improves social cognitive functions such as imitation-inhibition and perspective-taking. Although previous work shows that tDCS of the right IFC improves imitation-inhibition, its effects on perspective-taking have yet to be determined. In addition, the role of the TPJ and IFC in determining the Autism-Spectrum Quotient (AQ), which is a measure of autism spectrum traits, is still unclear. Thus, the current study performed tDCS on the right TPJ and the right IFC of healthy adults, and examined its effects on imitation-inhibition, perspective-taking, and AQ scores. Based on previous studies, we hypothesized that anodal tDCS of the right IFC and right TPJ would improve imitation-inhibition, perspective-taking, and the AQ score. Anodal tDCS of the right TPJ or IFC significantly decreased the interference effect in an imitation-inhibition task and the cost of perspective-taking in a perspective-taking task, in comparison to the sham stimulation control. These findings indicated that both the TPJ and the IFC play a role in imitation-inhibition and perspective-taking, i.e. control of self and other representations. However, anodal stimulation of the right TPJ and the right IFC did not alter participants’ AQ. This finding conflicts with results from previous brain imaging studies, which could be attributed to methodological differences such as variation in sex, age, and ASD. Therefore, further research is necessary to determine the relationship between the TPJ and IFC, and the AQ.